(3GdJShjb GdOhdjs - (3YHO GdSdGe(B, (3CHh bMas ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3ebOeGJ hbVGjG QFjSjI(B-(3HjFI GdJShjb GdOhdj(B-(3fXQjGJ GdJOhjd(B-(3WQb heSGQGJ ZRh GdCShGb GdOhdjI(B/(3GdCLfHjI(B-(3GSJQGJjLjI GdJShjb GdchfjI GdedGeM hGdCWQ GdYGeI(B-(3GdJShjb Gdchfj ddNOeGJ(B-(3GSJNHGQGJ GdJShjb GdOhdj(B-(3fXe GdESJNHGQGJ GdUfGYjI hJWhjQ GdbOQGJ GdJfGaSjI defXeGJ GdCYeGd(B-(3EOGQI GdJUOjQ(B-(3SjGSGJ GdefJL GdOhdj(B-(3SjGSI GdJhRjY GdOhdj(B-(3SjGSI GdEYdGf hGdJQhjL aj GdCShGb GdOhdjI(B-(3GdJSYjQ aj GdCShGb GdOhdjI(B-(3GHYGO GdJMhjd Hjf aQhY GdTQcGJ GdYGdejI heJYOOI GdLfSjGJ(B-(3GdJShjb GdOhdj ddNOeGJ(B((3fHPI SQjYg(B)s
(3GdedGMb U(B.189s
Keywords: (3GdJShjbs; (3GdJShjb GdOhdjs